2007
DOI: 10.5194/acp-7-3195-2007
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lead in single atmospheric particles

Abstract: Abstract. Three independent single particle mass spectrometers measured Pb in individual aerosol particles. These data provide unprecedented sensitivity and statistical significance for the measurement of Pb in single particles. This paper explores the reasons for the frequency of Pb in fine particles now that most gasoline is unleaded. Trace amounts of Pb were found in 5 to 25% of 250 to 3000 nm diameter particles sampled by both aircraft and surface instruments in the eastern and western United States. Over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 43 publications
3
44
2
Order By: Relevance
“…Ebert et al, 2000;EPA, 2002). Today, the dominant sources for Pb-rich particles are light aviation fuel (which still contains tetra-ethyl lead), emissions from coal combustion and lead smelters (Murphy et al, 2007). In contrast to previous CLACE campaigns, lot of helicopter traffic occurred in the direct vicinity of the Jungfraujoch station during CLACE 5.…”
Section: Pb Bearing Particlesmentioning
confidence: 77%
See 1 more Smart Citation
“…Ebert et al, 2000;EPA, 2002). Today, the dominant sources for Pb-rich particles are light aviation fuel (which still contains tetra-ethyl lead), emissions from coal combustion and lead smelters (Murphy et al, 2007). In contrast to previous CLACE campaigns, lot of helicopter traffic occurred in the direct vicinity of the Jungfraujoch station during CLACE 5.…”
Section: Pb Bearing Particlesmentioning
confidence: 77%
“…3). The fact that most Pb bearing particles contain this element only in minor or trace concentrations was also observed for total aerosol samples at a variety of locations by Murphy et al (2007).…”
Section: Pb Bearing Particlesmentioning
confidence: 91%
“…A few previous field studies have noted metal-rich 'industrial' IN (4,8,28,29). Lead, present in ~5% of ambient particles (30), has been shown to be a particularly efficient IN in the field and laboratory (21,29). Laboratory studies and improved emission inventories coupled to cloud formation models are needed to elucidate the global effect of anthropogenic particles on cirrus.…”
Section: (12)mentioning
confidence: 99%
“…The mass abundance of this component can be very low. Nevertheless, by in situ mass spectrometry measurements Murphy et al (2007b) found lead in 5 to 25 % of all analyzed particles in the upper troposphere. They discussed aviation fuel and coal combustion as a source for these particles.…”
Section: Pb-rich Particlesmentioning
confidence: 99%
“…They discussed aviation fuel and coal combustion as a source for these particles. A distinct internal contamination source for lead could not be discovered, but because of the ubiquitous distribution of trace amounts of lead in the environment (Murphy et al, 2007b) it cannot completely be excluded.…”
Section: Pb-rich Particlesmentioning
confidence: 99%